Contributions of Internal and External Variables in Non-Performing Financing Bank Muamalat for the Period of 2005-2021 - Sandi Mulyadi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
The purpose of this study is to describe the condition of internal and external variables for non-performing financing in the 2005-2021 period by using internal variables that are proxied by Operating Expenses (OE), Financing Deposit Ratio (FDR), Net Operating Margin (NOM), and Return On Equity (ROE), while external variables are proxied by Gross Domestic Product (GDP) and inflation. The method used in this research is descriptive quantitative by analyzing secondary data which is processed using Eviews 10 with the VECM method and using quarterly time series data from 2005-2021. The results of data processing using VECM show several findings, namely: the ROE, GDP, and inflation variables have a positive effect, then the FDR and NOM variables have a negative effect, while OE has no effect on non-performing financing in the long term, while in the short term all variables do not affect non-performing financing. performing financing. Meanwhile, based on testing using FEDV, the contribution to non-performing financing is OE (1.08%), FDR (0.89%), NOM (4.11%), ROE (0.95%), GDP (2.29%), and inflation (2.68%).